ANALYSIS OF THE LAW AGAINST CRIMINAL ACTS OF ELECTORAL DISTRICTS (Study of a general election the Mayor and Vice Mayor of Makassar) - Hakim, Andi Abdul (Journal of Humanity, 2014)
This research aims to know the effectiveness of the law enforcement against criminal cases in the general election for mayor of the city as well as the factors which affected analysis in this study using the method of the qualitative nature of the approach, that approach with a way to learn, pay attention to the quality and depth of the data obtained. After data analysis is finished, the results will be presented in a descriptive, i.e. with speak and describing what it is in accordance with the problems examined. The effectiveness of the law enforcement against criminal cases in the general election for mayor of the city is still very weak. The mechanism of reporting, and discussion of the results of the report on the level of integrated law enforcement (Gakkumdu), as well as the report of the examination to find out the criminal element in violation of 2005, Makassar city thus increasingly adds to the complicated handling of the crime in 2005. Factors that affect the police in tackling and dealing with criminal acts in 2005, in the city of Makassar is the length of the process of examination of an alleged criminal offence occurrence in 2005, has been with the examination report having to wait for the outcome of the recommendations of the report are Gakkumdu can be forwarded at the stage of investigation or not.